Futsal Playing Skill Level of Futsal Extracurricular Participants - Zusyah Porja Daryanto; Awang Roni Effendi (Champions: Education Journal of Sport, Health, and Recreation, 2023)
This research aims to determine the level of futsal playing skills of students participating in extracurricular futsal at SMA Muhammadiyah 1 Pontianak so that it can become a reference for preparing for the futsal championship. This research is descriptive research using a survey method for collecting data with test and measurement techniques. The subjects in this research were 18 futsal extracurricular students. The data collection technique uses a futsal playing skills test. The data analysis technique used is quantitative descriptive statistics with percentages. Based on the data analysis that has been carried out, it is obtained that the level of futsal playing skills of students participating in the futsal extracurricular at SMA Muhammadiyah 1 Pontianak is in the category of less than 1 student or equal to (5.56%), the category of less than 5 students or equal to (27, 78%), the medium category is 7 students or (38.89%), the good category is 4 students or (22.22%), and the very good category is 1 student or (5.56%). Overall, it can be concluded that the level of futsal playing skills of students participating in extracurricular futsal at SMA Muhammadiyah 1 Pontianak is mostly in the medium category